Fundamentals of Targeted Integrative Program Development for Rural Labor Market Growth in Surplus Regions - Rakhmatovich, Kholmuminov Shayzak (International Journal of Economics and Financial Issues, 2024)
This article introduces a systematic approach for developing a targeted comprehensive program aimed at enhancing the rural labor market (TCPDRLM) in labor-surplus regions of the Republic of Uzbekistan, within a socially oriented market economy. The paper outlines key interconnected principles for the development of TCPDRLM, including target orientation, complexity, integration, specificity, variability, realism, optimality, priority, delineation of powers and functions, limitations, targeting, controllability, and interconnectedness. Based on these principles, the article proposes interrelated sections for the program’s development, covering analytical and problematic aspects, target delineation, scientific and methodological frameworks, information management, modeling, software development, resource allocation, organizational and economic structuring, summary formulation, and legal considerations. Additionally, the article details the primary stages of TCPDRLM development, including setting objectives for the rural labor market (RLM), developing methodological and modeling frameworks for RLM analysis and forecasting, collecting statistical, marketing, and sociological data, compiling the TCPDRLM subprograms, obtaining approval for the RLM development program, and establishing organizational, economic, and legal mechanisms for program implementation and adjustment. The article's scientific contribution lies in the formulated methodology for TCPDRLM development in the rural labor market.